If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 5 = -4x + -19 Reorder the terms: 5 + -6x = -4x + -19 Reorder the terms: 5 + -6x = -19 + -4x Solving 5 + -6x = -19 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + -6x + 4x = -19 + -4x + 4x Combine like terms: -6x + 4x = -2x 5 + -2x = -19 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + -2x = -19 + 0 5 + -2x = -19 Add '-5' to each side of the equation. 5 + -5 + -2x = -19 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -19 + -5 -2x = -19 + -5 Combine like terms: -19 + -5 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| 5x^3=120 | | .57x=18 | | (-5x^2)-(-9x^2)= | | 3x+3x+-1=4x+9 | | -4(m+6)=.8 | | p/9-5=2 | | 4(x+7)+3x=12+4x-5 | | (2y+7)(8y^2-6y+1)=0 | | 4n+9=2n+13 | | 142=5x-6(-4x+15) | | 3t+12=2t+14 | | -x^2+4y^2-20x+8y-92=0 | | 4q=x+12 | | x+10+3(x+6)=180 | | 4x-(-12x+24y)y=4 | | (3x+5)(5x^2+4x+11)=0 | | 2(x+12)=x-9 | | 10x+25y=190 | | y=(x-1)(x+1)(x-5) | | (3y+3)(4y^2+5y+20)=0 | | 12x^2-7+1= | | 4x^2+y^2-48x+140=0 | | x^2+y^2+8x+4y+1=0 | | x^2+y^2+8x+4y+2=0 | | 3x^-1/4x^4 | | 5y-(3y-2)=0 | | (2x-14)/12-(2x-1)/18=2/9(3x-5) | | p^2+0p-30=0 | | x^2+y^2+8x+4y=0 | | (2x+1)(x^2-6x+2)=0 | | 2n^4*6n^4= | | -7x-4=8x+8 |